The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1111/j.1440-1746.2007.05024.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of adjunctive ketamine on sphincter of Oddi motility in humans

Abstract: Ketamine at 20 mg did not significantly affect SOM parameters. Further studies are required to confirm our preliminary findings before ketamine can be added to the armamentarium of agents used for performance of sphincter of Oddi manometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…However, a recent study by Varadarajulu et al showed that there were no significant changes in flow resistance of the sphincter of Oddi in humans receiving ketamine for sedation [7].…”
Section: Discussionmentioning
confidence: 98%
“…However, a recent study by Varadarajulu et al showed that there were no significant changes in flow resistance of the sphincter of Oddi in humans receiving ketamine for sedation [7].…”
Section: Discussionmentioning
confidence: 98%
“…suggests that ketamine stimulates opiate receptors and is associated with an increase in flow resistance through the sphincter of Oddi [ 45 ]. On the contrary, the results of sphincter of Oddi manometry in human subjects receiving low-dose ketamine for endoscopy does not support this claim [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective investigation of patients receiving ketamine for sedation during endoscopic retrograde cholangiopancreatography, the authors were unable to visualise any change in pressures or motility of the sphincter of Oddi post ketamine use and there was no SSC, 8 further indicating that, in the bolus doses used, ketamine is a safe drug to use for sedation purposes.…”
mentioning
confidence: 99%